Two protocols to synchronize the oestrus of lactating ewes using progestogens - Espinoza Molina, Saúl (2022)
The aim of this study was to evaluate two protocols for oestrus synchronization using intravaginal progestogens. In the study, 64 ewes with lambs at foot of 30-40 days old were used. The animals were assigned to two groups: (T1): application of a short synchronization protocol (6 days) with suppression of suckling for 30 hours (n1=32) and (T2): application of a long or conventional protocol (12 days) with suppression of suckling for 54 hours (n2=32). Fixed-time artificial insemination (FTAI) was performed with refrigerated semen through the transcervical route at the end of temporary weaning. The pregnancy rate without heat return at 16-17 days post-FTAI, pregnancy rate at 41 days by ultrasound, pregnancy rate at 90 days by balloting and type of delivery were determined. The rate of non-return to oestrus at 15-17 days post-FTAI was 81.25% for T1 and 87.50% for T2 (p<0.05). Likewise, the pregnancy percentages by ultrasound and by balloting were statistically similar between treatments. The twin birth rate was slightly, but not significantly different in T2 (26.92%) than in T1 (19.2%). The results show that when applying a short synchronization protocol, similar results are achieved as when applying the conventional synchronization protocol and with the advantage that it is carried out in less time.